Effects of protein sources at sahur on anaerobic power and strength during Ramadan in combat sport athletes: A single blind, randomized, placebo-controlled, counterbalanced crossover study design - Abdullah Demirli; Süleyman Ulupınar; Ayşe Türksoy Işım; Alay Kesler; Merve Terzi; Cebrail Gençoğlu; Serhat Özbay; Melenco Ionel; Ibrahim Ouergui; Luca Paolo Ardigò (PLoS ONE, 2026)
This study investigated the acute effects of different protein sources consumed at sahur on anaerobic power and strength performances in trained male combat sport athletes during Ramadan fasting. Using a single blind, randomized, placebo-controlled, counterbalanced crossover study design, 24 male combat sports’ athletes (mean age: 27.3 ± 3.8 years, Tier 3 national level) completed four experimental conditions: (1) non-fasting control, (2) fasting + placebo (maltodextrin), (3) fasting + whey protein isolate (WPI), and (4) fasting + micellar casein (MC). In each condition, a standardized sahur meal (6.3–7.7 kcal/kg body weight) and supplementation (0.4 g/kg for WPI/MC and 0.4 g/kg for Placebo) were administered. Physical Performances was assessed 11–13 hours post-sahur (or 3–5 hours post-lunch for control) including the Wingate anaerobic test, bench press, leg press, and countermovement jump (CMJ), and handgrip strength tests. Ramadan fasting significantly lowered Wingate peak power, mean power, and bench press strength compared to the non-fasting control. MC supplementation reduced these declines, outperforming WPI and the placebo in peak power and mean power, and surpassing the placebo in bench press strength, although not WPI. Leg press, countermovement jump, and handgrip strength showed no significant differences across conditions. MC supplementation at sahur provides partial protection against fasting-induced declines in anaerobic power and upper body endurance, but does not fully restore performance to non-fasting levels. These findings emphasize the importance of protein timing and selection in mitigating performance decrements during Ramadan fasting, highlighting the need for further research on optimal nutritional strategies for athletes training and competing under fasting conditions.